Az 1968-as csehszlovákiai bevonulás a 31. harckocsiezred szemszögéből - Csík Ádám Lajos (2018)
In 1968 Czechoslovakia within the eastern bloc was taking the lead in the field of political and social reforms to develop "human-faced socialism". The political elite of the Soviet Union was seriously concerned about it, therefore during the spring and summer of 1968, continuous meetings, consultations and negotiations took place between the Warsaw “group of five” and Czechoslovakia. In spite of the negotiations the Czechoslovak leadership could not be forced to follow the instructions given by the five. That is why the Soviet leadership had made the ultimate decision, that is, to intervene Czechoslovakia, involving its allies in the military action. The purpose of my presentation is to present the preparation of the Hungarian People's Army for the military action and its role in the intervention, as well as the Army’s everyday in foreign land and finally the withdrawal from Czechoslovakia. My further aim is to present the political and combat preparation of the troops involved in the operation, as well as the everyday life of the Czechoslovakian people at that time, their mood and attitude towards the Hungarian troops, relying on primary sources, from the perspective of the patrolling soldiers.